"Sofrem duramente os operários" : indústria têxtil, classe operária e poder disciplinar em Neópolis (1946-1955) - Cardoso, Mércia Santos (2023)
The birth of factories changed society, reshaping social relations, habits and, consequently, everyday life. The industrial process created the factory environment and, with that, a new form of work emerged, where people became salaried workers, dedicating hours of their daily time to factory work. In this sense, the rigorous rhythms, as well as the long working hours, made up a daily life in which most of the daily life took place within the walls of the factories. In Brazil, industrialization along the lines of the factory system gained strength during the first years of the republic. In Sergipe, textile factories played a key role in the economic development of the state, providing social, political and cultural changes. Thus, this research seeks to understand aspects of the daily life of the textile workers in Neópolis during 1946-1955. To know these workers, labor claims filed against Peixoto, Gonçalves & Cia were used, as well as documents produced by workers reporting their dissatisfaction with the Textile Company (both factories founded in 1906). The sources used come from the General Archive of the Judiciary of Sergipe (AGJSE). To understand these relationships, the theoretical framework of this research is based on the concept of disciplinarization, proposed by Michel Foucault, aiming to understand the process of disciplinarization in the daily life of textile workers in Neópolis.